2017
DOI: 10.1038/srep41049
|View full text |Cite
|
Sign up to set email alerts
|

Gradient-Hierarchic-Aligned Porosity SiOC Ceramics

Abstract: This work describes a simple technique to produce porous ceramics with aligned porosity having very high permeability and specific surface area. SiOC-based compositions were processed from blends of three types of preceramic polymer and a catalyst, followed by curing and pyrolysis. The heating applied from the bottom of molds promoted the nucleation, expansion and rising of gas bubbles, and the creation of a ceramic matrix with axially oriented channels interconnected by small round pores. The samples were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 49 publications
(100 reference statements)
5
29
0
Order By: Relevance
“…The polymer pyrolysis method offers another important advantage compared to the traditional powder processing of ceramic materials: a wide range of forming techniques are available to shape the components in the polymeric state which is then retained in the final ceramic state. Consequently, PDCs fibers, films, ceramic matrix composites, MEMS, and a variety of macro‐, meso‐, and micro‐porous ceramics (even with lotus‐type porosity) have been obtained via the PDC route and several comprehensive reviews are available on this topic . Concerning the processing of porous materials, the synthesis of PDC aerogels has been recently proposed by some of us and SiC, SiOC, and SiCN aerogels have been obtained and characterized …”
Section: Introductionmentioning
confidence: 99%
“…The polymer pyrolysis method offers another important advantage compared to the traditional powder processing of ceramic materials: a wide range of forming techniques are available to shape the components in the polymeric state which is then retained in the final ceramic state. Consequently, PDCs fibers, films, ceramic matrix composites, MEMS, and a variety of macro‐, meso‐, and micro‐porous ceramics (even with lotus‐type porosity) have been obtained via the PDC route and several comprehensive reviews are available on this topic . Concerning the processing of porous materials, the synthesis of PDC aerogels has been recently proposed by some of us and SiC, SiOC, and SiCN aerogels have been obtained and characterized …”
Section: Introductionmentioning
confidence: 99%
“…The Barrett‐Joyner‐Halenda (BJH) used to obtain the pore size distribution (PSD). In a previous study, the SSA values were found ~120 m 2 /g for W and ~660 m 2 /g for W‐HF and PSD demonstrated that while sample W was mostly mesoporous, W‐HF had broad pore size distribution in both micro and mesopore range (see Figure ).…”
Section: Methodsmentioning
confidence: 82%
“…The samples were prepared following the procedure given in the literature . All the starting chemicals were used as received: Hydrotalcite, (LDH: Mg 6 Al 2 (CO 3 )(OH) 16 ·4H 2 O), vinyl‐terminated polydimethylsiloxane (PDMS, Gelest, USA, CAS# 68083‐19‐2) a cyclic 2,4,6,8‐tetramethyl‐2,4,6,8‐ tetravinlycyclotetrasiloxane (TMTVS 97%, Alfa Aesar, USA, CAS# 2554‐06‐5), and polymethylhydrosiloxane (PHMS, CAS# 63148‐57‐2, Gelest,USA), Platinum ‐ divinyltetramethyldisiloxane complex, ~Pt 2% in xylene (Sigma‐Aldrich, USA, CAS# 68478‐92‐2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, initially formed microbeads can be infiltrated by the same chemical composition derivable PP. 4,211 | 2963 VAKIFAHMETOGLU ET AL.…”
Section: Perspectivesmentioning
confidence: 99%